BONE COMPOSITION AND THE BIRTH OF QUANTITATIVE CHEMISTRY - Natale Gaspare De Santo; Rosa Maria De Santo; Rado Pišot; Carmela Bisaccia; Alessandra Perna; Mariano Bizzarri; Vito Andrea Di Leo; Giancarlo Bilancio; Massimo Cirillo (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2011)
Bone is an important tissue for space specialists since it undergoes significant changes under microgravity conditions and its healing is slow. Bone has been considered a special tissue since the very inception of medical theories. In Akragas, Empedocles' (493-432 BC) hypothesis regarding bone was that it was made of two parts earth, two parts water and four parts fire, thus marking the beginning of quantitative chemistry.